2016
DOI: 10.3109/10641963.2015.1089882
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol lowers blood pressure in spontaneously hypertensive rats via calcium-dependent endothelial NO production

Abstract: Resveratrol increases endothelial NO production to improve endothelial dysfunction and lowers BP in hypertensive rats, which depends on calcium-eNOS activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
1
15
1
3
Order By: Relevance
“…Due to its natural and safe origin, the use of RESV has been reported in complications during pregnancy (22), including gestational diabetes mellitus (23). Of particular interest to our current study, the anti-hypertension property of RESV has also been demonstrated in a number of studies employing both animal and clinical studies (13, 14, 15, 16, 17). Given its widely reported anti-hypertensive function, we therefore also employed RESV in the current clinical trial among pregnant women affected by PE, with the hypothesis that RESV could also exhibit benefits in relieving hypertension in pregnancy-induced PE.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Due to its natural and safe origin, the use of RESV has been reported in complications during pregnancy (22), including gestational diabetes mellitus (23). Of particular interest to our current study, the anti-hypertension property of RESV has also been demonstrated in a number of studies employing both animal and clinical studies (13, 14, 15, 16, 17). Given its widely reported anti-hypertensive function, we therefore also employed RESV in the current clinical trial among pregnant women affected by PE, with the hypothesis that RESV could also exhibit benefits in relieving hypertension in pregnancy-induced PE.…”
Section: Discussionmentioning
confidence: 85%
“…In a pregnant mouse model with reduced blood supply to the uterus, RESV increased uterine artery blood flow velocity and fetal weight (15). In spontaneously hypertensive rats, RESV could lower blood pressure through production of calcium-dependent endothelial NO (16). In addition, in a recent clinical trial among patients with primary hypertension, RESV was able to supplement standard anti-hypertensive therapy to effectively reduce blood pressure to normal levels (17).…”
Section: Introductionmentioning
confidence: 99%
“…This claim was backed up by reports of AMPK-dependent phosphorylation of eNOS (on Ser1177) following the exposure of cultured endothelial cells to agonists such as the vascular endothelial growth factor (VEGF) [ 9 ] and adiponectin [ 10 ], or pharmacological agents including peroxisome proliferator-activated receptor (PPAR) agonists [ 11 ] and statins [ 12 ]. Similar reports were also published using AMPK activators such as 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) [ 13 ] and metformin [ 14 , 15 ], or natural polyphenols like amurensin G [ 16 ] or resveratrol [ 17 ]. However, the effects are generally weak and much less impressive than the stimulation seen in response to hypoxia [ 7 ], shear stress [ 18 , 19 , 20 ], and thrombin [ 21 ] which result in robust AMPK activation.…”
Section: Introductionmentioning
confidence: 56%
“…Resveratrol is an activator of SIRT1, which promotes expression and activity of eNOS to improve ACh‐mediated relaxation in rat aorta . Furthermore, in the isolated aorta of SHRs, resveratrol enhances ACh‐mediated relaxation ex vivo by increasing eNOS phosphorylation . Resveratrol treatment also enhances NO production in primary bovine aortic endothelial cells, while lowering blood pressure in SHRs after 4 weeks’ administration.…”
Section: Miscellaneous Agentsmentioning
confidence: 99%